The Oxygen Blackout in the Amazon and the deaths by asphyxiation in patients with Covid-19 - Psychological sequelae - Honorato, Eduardo Jorge Sant Ana (Saúde em Redes, 2021)
Article reporting situations of psychological demands in the middle of the pandemic, in the epicenter of Manaus